METHODS OF ANALYSIS OF CAPITAL STRUCTURE AND ITS IMPACT ON PROFITABILITY (ON THE EXAMPLE JSC «SUN InBev UKRAINE») - Шубіна , Світлана; Іщенко , Тетяна; Іщенко , Катерина; Мірошник, Олексій (Socio-economic relations in the digital society, 2019)
The article discusses the technique and analysis of capital structure and its impact on the profitability of the company; presents assessment of financial indicators that affect the profitability of the entity; reasonable relationship between financial leverage and risk enterprise. Deals with the main areas of strategic capital structure policy in the management of profitability of the entity: determination of the optimal proportions of the enterprise for the use of own and attracted capital (optimal structure of capital); ensuring the attraction of the necessary types and amounts of capital to achieve the estimated indicators of its structure; prognostication of such a structure of capital, which, at its lowest cost, would enable the company to maintain stable incomes and obtain expected profitability.